Global review of the H5N8 avian influenza virus subtype - Rafique, Saba; Rashid, Farooq; Mushtaq, Sajda; Ali, Akbar; Li, Meng; Luo, Sisi; Xie, Liji; Xie, Zhixun (Frontiers in Microbiology, 2023)
Orthomyxoviruses are negative-sense, RNA viruses with segmented genomes that are highly unstable due to reassortment. The highly pathogenic avian influenza (HPAI) subtype H5N8 emerged in wild birds in China. Since its emergence, it has posed a significant threat to poultry and human health. Poultry meat is considered an inexpensive source of protein, but due to outbreaks of HPAI H5N8 from migratory birds in commercial flocks, the poultry meat industry has been facing severe financial crises. This review focuses on occasional epidemics that have damaged food security and poultry production across Europe, Eurasia, the Middle East, Africa, and America. HPAI H5N8 viral sequences have been retrieved from GISAID and analyzed. Virulent HPAI H5N8 belongs to clade 2.3.4.4b, Gs/GD lineage, and has been a threat to the poultry industry and the public in several countries since its first introduction. Continent-wide outbreaks have revealed that this virus is spreading globally. Thus, continuous sero- and viro-surveillance both in commercial and wild birds, and strict biosecurity reduces the risk of the HPAI virus appearing. Furthermore, homologous vaccination practices in commercial poultry need to be introduced to overcome the introduction of emergent strains. This review clearly indicates that HPAI H5N8 is a continuous threat to poultry and people and that further regional epidemiological studies are needed.